The Political Roles and Leadership of Women in Establishing the Khilafah Islamiyah ( epistemological Interpretation of Ex - HTI's Member ) - Ruwaidah (Fak. Ushuluddin dan Pemikiran Islam UIN Sunan Kalijaga, 2021)
et,1/adil,c.1